(untitled) (American Journal of Islam and Society, 1991)
The Muslim Religious Board for Central Asia and Kazakhstan organized an international conference in Tashkent, the capital city of Uzbekistan, in connection with the observances of the twelfth centenary of the birth of Imam Abu ’Isa Muhammad Ibn ’Isa al Tirmidhi, a native son. The conference was attended by scholars from the Soviet Union and nearly 100 delegates from overseas. The keynote address, which was also the conference’s theme, was delivered The American Journal of Islamic Social Sciences Vol. 8, No. 1 1991 185 by the Board’s Chairman Mufti Muhanunad Sadyq Muhammad Yusuf. He presented a detailed account of the Imam’s work, e pecially the well-known book Al Jami’ al Sahih, and its impact on the contemporary world. The scholars stressed the need for greater attention to research and study of the Sunnah of the Prophet Muhammad (SAAS). They also adopted a number of recommendations, including a call for greater attention to research on the hadith in order to facilitate its effective application in the everyday lives of Muslims. This, it was observed, would contribute toward the assertion and developoment of Islamic values throughout the ummah ...